2014
DOI: 10.1159/000367862
|View full text |Cite
|
Sign up to set email alerts
|

Previous Cancer and/or Lymphoma in Patients with Refractory IBD - Con: Anti-TNF or Conventional Immunosuppressive Treatment

Abstract: Patients with IBD and prior cancer are at increased risk of developing recurrent or de novo cancer. Depending on the type of malignancy, risk factors include IBD itself, age, environmental factors, genetic susceptibility and exposure to immunosuppressants (IMS), namely thiopurines, methotrexate and anti-TNFα biologics. The procarcinogenic effect of IMS depends on the type of drug and length of exposure. Thiopurines increase the rates of nonmelanoma skin cancer and lymphomas. Methotrexate is less harmful, but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Compared with the model group, qPCR demonstrated that the levels of inflammatory cytokines, including TNF-α and IL-6, were significantly increased in the NECA group; however, there were no significant differences in the decreased expression levels of TNF-α and IL-6 between the APCP and model groups. TNF-α is a pro-inflammatory cytokine secreted by Th17 cells in IBD and IBD-associated cancer (45,46). In addition, IL-6 is one of the most important pro-inflammatory cytokines mainly produced by myeloid cells and was identified as a key promoter of carcinogenesis (47).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the model group, qPCR demonstrated that the levels of inflammatory cytokines, including TNF-α and IL-6, were significantly increased in the NECA group; however, there were no significant differences in the decreased expression levels of TNF-α and IL-6 between the APCP and model groups. TNF-α is a pro-inflammatory cytokine secreted by Th17 cells in IBD and IBD-associated cancer (45,46). In addition, IL-6 is one of the most important pro-inflammatory cytokines mainly produced by myeloid cells and was identified as a key promoter of carcinogenesis (47).…”
Section: Discussionmentioning
confidence: 99%
“…There is heterogeneity in natural history of IBD with varying risks of recurrence of disease-related symptoms after therapy cessation. Comprehensive models that can predict this outcome may be helpful in identifying those at highest risk for IBD relapse, and consequently most likely to require early re-initiation of immunosuppressive therapy for IBD after the index cancer diagnosis 29, 30, 66 . While many existing guidelines recommend avoiding immunosuppression for 5 years after index cancer 2429 , our data may provide reassurance that there is no increased risk.…”
Section: Discussionmentioning
confidence: 99%
“…Malignancy was reported in only one of 297 (0.3%) patients treated with placebo (squamous cell carcinoma). 7 While expert consensus recommends avoiding anti-TNF exposure for 5 years after treatment of a malignancy, 21 it is not yet clear if vedolizumab should abide by the same rule of thumb.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%